Effect and safety of cytokine-induced killer (CIK) cell immunotherapy in patients with breast cancer: A meta-analysis. Issue 42 (October 2017) - Hu, Jianxin; Hu, Junfeng; Liu, Xiandong; Hu, Chao; Li, Ming; Han, Wei
Abstract: Background: Breast cancer (BC) is considered a systemic disease with a primarily locoregional component. The accumulation of basic researches and clinical studies related to cytokine-induced killer (CIK) cells has confirmed their safety and feasibility in treating BC. By searching the PubMed, Embase, CNKI, and Wanfang databases, we conducted a meta-analysis to assess the efficacy and safety of DC/CIK plus chemotherapy regimen (Exp) compared with chemotherapy (Con) alone regimen for breast carcinoma. Studies were pooled, and the relative risk (RR) and its corresponding 95% confidence interval (CI) were calculated. Methods: Eleven relevant articles were included in this meta-analysis. We observed that complete response (CR) (RR = 1.54, 95% CI: 1.09–2.19, P heterogeneity = .994, I 2 = 0%), partial response (PR) (RR = 1.33, 95% CI: 1.11–1.59, P heterogeneity = .802, I 2 = 0%) and overall response rate (ORR) (RR = 1.37, 95% CI: 1.20–1.57, P heterogeneity = .619, I 2 = 0%) in BC patients treatment with DC/CIK plus chemotherapy regimen was improved than that with chemotherapy alone. There was no difference in the incidence of leukopenia, thrombocytopenia, hair loss, nausea/vomiting, hepatic complications, and neurologic complications in BC patient's treatment with DC/CIK plus chemotherapy regimen and with chemotherapy alone. Results: Compared to chemotherapy alone, DC/CIK plus chemotherapy treatment significantly increased CR, PR, and ORR; however, there was no difference between the safeties. Conclusion: DC/CIK plus chemotherapy treatment may be a valuable new option for the treatment of breast carcinoma in women. The present study, therefore, provides valuable information to help physicians make treatment decisions for their patients with BC.